Effect of extraction pH and temperature on yield and physicochemical properties of gelatin from Atlantic salmon (Salmo salar) skin - Renaldi, Gerry; Sirinupong, Nualpun; Samakradhamrongthai, Rajnibhas Sukeaw (Agriculture and Natural Resources, 2022)
Importance of the work: The use of different conditions in the gelatin extraction affected the yield and physicochemical properties of the resultant gelatin. Objectives: To investigate the effects of different extraction levels of pH and temperature on the properties of gelatin from Atlantic salmon (Salmo salar) skin. Materials & Methods: Different extraction levels for pH (4, 6, 8) and temperature (50 °C, 60 °C, 70 °C) were investigated to extract the gelatin and the results were analyzed regarding the yield and physicochemical properties. Results: The extraction pH and temperature significantly affected the yield and physicochemical properties of the gelatin extracted from Atlantic salmon skin. Extraction at pH 4 and 50°C provided the highest yield (6.20±0.09%), while the extraction at pH 6 and 50 °C resulted in the gelatin containing 9.20±0.37% protein and 73.60±0.46% hydroxyproline content, with the highest gel strength (198.67±4.51 g). The gelatin having values of L*, a* and b* of 81.89±1.09, -0.47±0.01 and 3.07±0.11, respectively with a gelling temperature of 12.54±0.07 °C and a melting temperature of 23.82±0.14 °C. The sodium dodecyl sulfate-polyacrylamide gel electrophoresis protein pattern analysis showed that the extraction with basic conditions hydrolyzed the protein more than with acidic conditions. Main finding: The use of different levels of pH and temperatures should be taken into consideration prior to gelatin extraction, especially for gelatin extraction from fish skin, to obtain gelatin with the preferred yield and properties for further application.